2021
DOI: 10.1002/ijgo.13720
|View full text |Cite
|
Sign up to set email alerts
|

Early abortion care during the COVID‐19 public health emergency in Ireland: Implications for law, policy, and service delivery

Abstract: Abortion in early pregnancy became available in Ireland in January 2019, following decades of campaigning by activists and civil society organizations for the repeal of the country's constitutional abortion ban. 1 The new law-the Health (Regulation of Termination of Pregnancy) Act 2018-provides for access to abortion on request up to 12 weeks of pregnancy, dated from the last menstrual period (LMP). 2 Early abortion care initially involved two face-to-face visits with a medical practitioner, separated by a 3-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The results of this study indicated that the pooled proportion of abortion care services utilization in Ethiopia was reduced by 19.39%. This finding was supported by findings of previous studies done in Belgium [ 75 ] and Ireland [ 76 ], which reported a substantial reduction in abortion care services during COVID-19. The reason for the reduction in abortion care is that women perhaps engaged less in risky sexual behavior during the COVID-19 pandemic, and were challenged less with unexpected pregnancies [ 77 , 78 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study indicated that the pooled proportion of abortion care services utilization in Ethiopia was reduced by 19.39%. This finding was supported by findings of previous studies done in Belgium [ 75 ] and Ireland [ 76 ], which reported a substantial reduction in abortion care services during COVID-19. The reason for the reduction in abortion care is that women perhaps engaged less in risky sexual behavior during the COVID-19 pandemic, and were challenged less with unexpected pregnancies [ 77 , 78 ].…”
Section: Discussionsupporting
confidence: 89%
“…studies done in Belgium [75] and Ireland [76], which reported a substantial reduction in abortion care services during COVID-19. The reason for the reduction in abortion care is that women perhaps engaged less in risky sexual behavior during the COVID-19 pandemic, and were challenged less with unexpected pregnancies [77,78].…”
Section: Plos Onementioning
confidence: 99%
“…In April 2020, Ireland's Department of Health issued temporary emergency provisions, intended to only last for the duration of the COVID-19 pandemic, which allow the two mandatory consultations for abortion to take place remotely ( 21 ). Medical practitioners may choose to require that at least one of the consultations occur in-person, but the provisions recommend that in-person consultations be kept to a minimum during the COVID-19 public health emergency ( 21 – 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent article by Spillane et al 1 discussed the experience of the Irish Family Planning Association in implementing early abortion care via telemedicine in Ireland during the COVID‐19 pandemic. The study attests to the efforts needed to guarantee access to essential health services for women and girls during a public health emergency.…”
mentioning
confidence: 99%
“…Brazil leads the world in the number of maternal deaths due to COVID‐19 4 . The Ministry of Health is halting vaccination of pregnant women and the Supreme Court declined the petition asking for priority vaccination access for pregnant women 5 . The cases of Ireland and Brazil demonstrate how urgent it is to guarantee abortion access via telemedicine, protect healthcare providers, and expand access to essential care for the most vulnerable women and girls in our societies.…”
mentioning
confidence: 99%